STUDY OF MOTOR DEVELOPMENT: AGE RELATIONSHIP BETWEEN MOTOR AND GENERAL SCHOOL CHRONOLOGICAL AGE (Fiep Bulletin - online, 2013)
Motor development according to Gallahue; Ozmun (2005) is the change in motor behavior continues throughout the life cycle, provided by the interaction between the needs of the task, the individual's biology and environmental conditions. In middle childhood, school age, is the stage where the child emerges a breakthrough in their motor development and learning. In this context I came up to school and physical education classes, since this should bother to justify the practice of any motor activity. Thus aim of this study was to know the level of motor development by comparing the motor age with chronological and Motor Quotient general students of a public school, the peripheral region, the city of Montes Claros-MG. This study consists of an exploratory research, a descriptive, cross-sectional and quantitative data analysis. The study population was composed of students aged 8 and 9 years. The sample consisted of 20 students, of both sexes. The instrument used for data collection was the Motor Development Scale (EDM), validated by Rosa Neto (2002). Students at the school had delayed in all variables of motor development, with a delay of your General Motor Age (92.50) compared with chronological age (109.50). According to these results there is a delay of approximately 1 year and 5 months which equates to 17 months in its development engine. The average General Motor Quotient (GMQ) was classified as Low Normal. In this sense it is necessary to develop an intervention plan that can cover all the variables under consideration, the physical education teacher is essential, because in her class can provide meaningful experiences to all fields of human movement.
Keywords: Motor development; Chronological age; School.